Perlindungan Hukum terhadap Kepemilikan Tanah dalam Sengketa Sertifikat Hak Milik atas Tanah di Cikarang Selatan, Kabupaten Bekasi, Jawa Barat (Putusan Perkara Nomor: 285/Pdt.G/2023/PN Ckr) - Putri, Adinda Alvita; Suardi, Suardi (PT Elaborium Elevasi Indonesia, 2025)
This study examines the legal protection of land ownership in a land certificate dispute case in South Cikarang, Bekasi Regency, focusing on the District Court Decision Number 285/Pdt.G/2023/PN Ckr. The dispute involves the plaintiff as the legitimate owner of the land, proven by three lawfully issued land certificates from the 1980s to 1990s, and the defendant who obtained new certificates through allegedly invalid deeds of sale based on fictitious data. The legal issues analyzed include the court's legal reasoning in determining the existence of unlawful acts and the effectiveness of legal protection for rightful landowners. This research employs normative and empirical legal methods with a case approach, focusing on the court’s ratio decidendi. The findings reveal that the court fully granted the plaintiff’s claims by declaring the defendant’s certificates null and void, recognizing administrative negligence by the Ministry of Agrarian Affairs and Spatial Planning, and awarding substantial compensation. The ruling reaffirms the importance of due diligence in land administration and serves as an important precedent for legal protection of legitimate landowners in Indonesia.